2022
DOI: 10.1155/2022/8460121
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of TNF-α and JNK Signaling Pathway Can Reduce Paclitaxel-Induced Apoptosis of Mouse Cardiomyocytes

Abstract: Paclitaxel (PTX) is a widely used chemotherapeutic drug for treating tumors. However, studies have shown that it can cause cardiac problems such as arrhythmia, myocarditis, chronic cardiomyopathy, and heart failure. Therefore, it is essential to study the mechanism behind the cardiotoxicity of PTX in tumor treatment. In this study, we initially injected PTX into mice to establish a myocardial cell apoptosis model to observe the degree of damage to mouse myocardium caused by PTX. Upon determining the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
3
2
Order By: Relevance
“…Since TNF-α is a major activator of NF-κB, the decreased expression in our study likely resulted in the suppression of this canonical proinflammatory signaling pathway [31]. In contrast to our findings, paclitaxel administration increased myocardial TNF-α concentration and apoptosis in mice as discussed in [16]. In this study, paclitaxel was administered every three days for three months via intraperitoneal injection, while our protocol included a 10 mg/kg paclitaxel dose for five days in an oral formulation by gavage [19].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Since TNF-α is a major activator of NF-κB, the decreased expression in our study likely resulted in the suppression of this canonical proinflammatory signaling pathway [31]. In contrast to our findings, paclitaxel administration increased myocardial TNF-α concentration and apoptosis in mice as discussed in [16]. In this study, paclitaxel was administered every three days for three months via intraperitoneal injection, while our protocol included a 10 mg/kg paclitaxel dose for five days in an oral formulation by gavage [19].…”
Section: Discussioncontrasting
confidence: 73%
“…Importantly, paclitaxel dosing of 25 µg vs. 125 µg on a coated stent determined the myocardial concentration of the drug, with an approximately 10-fold increase with the high-dose stent compared to the low-dose used [33]. As opposed to previous research [16,21], in the present work paclitaxel administration alone did not affect any of the measured molecules in the ventricles without isoproterenol-induced damage. Others also demonstrated that paclitaxel did not induce any myocardial damage in isolated rat hearts during normoxia [8].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%